PENGARUH PROFITABILITAS, ASSET QUALITY, CAPITAL STRUCTURE DAN MARKET RESPONSE TERHADAP KOMPENSASI EKSEKUTIF SEKTOR PERBANKAN YANG TERDAFTAR DI BURSA EFEK INDONESIA TAHUN 2015-2019 - Priscilia Andriana Lengo; Taufik Hidayat (Ibs Press, 2024)
The purpose of this research is to determine the impact of profitability, asset quality,capital structure and market response on executive compensation of 33 banks sector in Indonesia Stock Exchange period 2015 -2019. Financial Performance of banks used in this study is Profitability measured by Return On Asset (ROA), Asset quality measured by Non Performing Loan (NPL), capital structure measured by Capital Adequacy Ratio (CAR), and Market Response measured by Price Earning Ratio (PER). The result of this study showed that Profitability (ROA) has a positive significant to executive compensation, Asset quality (NPL) and Capital structure (CAR) has no significant effect on executive compensation. While market response (PER) has a negative significant to executive compensation.